2008
DOI: 10.3354/meps07534
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and functional changes associated with long-term recovery from organic enrichment

Abstract: The recovery of a soft sediment benthic invertebrate community from high levels of organic enrichment was evaluated after removal of farmed fish at an Atlantic salmon Salmo salar culture site in southeast Tasmania. Although the pattern of recovery followed established successional principles, after 36 mo neither communities under or at the edge of cages, nor communities 10 m from the edge of the cage, had attained a structure equivalent to that of the reference communities. In the first few months there was li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…Additionally, biological indicators have been proposed for monitoring the environmental changes resulting from aquaculture. For example, changes of benthic macrofauna assemblages are generally recommended as a proxy for monitoring the impacts of cage farming (Macleod et al 2008, Yoon et al 2009, Jung et al 2016. However, investigation of the benthic community using video surveillance and the identification of macrofauna and meiofauna to the level of individual species is expensive and requires professional skill to make an accurate assessment of the impact (Castine et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, biological indicators have been proposed for monitoring the environmental changes resulting from aquaculture. For example, changes of benthic macrofauna assemblages are generally recommended as a proxy for monitoring the impacts of cage farming (Macleod et al 2008, Yoon et al 2009, Jung et al 2016. However, investigation of the benthic community using video surveillance and the identification of macrofauna and meiofauna to the level of individual species is expensive and requires professional skill to make an accurate assessment of the impact (Castine et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Macrofauna communities that exhibit a natural diversity, have a range of species with different biology, and so with different active biological transport traits [119,120]. Conversely, sediments affected by organic enrichment sources, such as fish farming, show less diverse macrofauna communities mainly composed by small opportunistic species with lower active biological transport activity [44,96,121]. This results in decreased metabolic capacity of the sediment, which may not be able to put up with the high OM loads derived from the fish farming activity, and may result in increased accumulation of organic waste products [122].…”
Section: Assessing Loss On Ecosystem Functioning Due To the Alteratiomentioning
confidence: 99%
“…However, if the species lost is a keystone species, its removal can have a notable decrease in the performance of the process [132] (Figure 4). Similarly, as regards benthic recovery after the cessation of the fish farming, the restoration of ecosystem functions may be a more useful indicator of recovery than the community equivalence with unpolluted areas [121].…”
Section: Assessing Loss On Ecosystem Functioning Due To the Alteratiomentioning
confidence: 99%
See 1 more Smart Citation
“…Trait-based approaches have been used to assess various anthropogenic pressures on streams and rivers, including WWTP effluents (Charvet et al 1998, Lecerf et al 2006, sediment toxicity (Archaimbault et al 2010), and multiple stressor gradients (Dolédec et al 1999, Usseglio-Polatera and Beisel 2002, Gayraud et al 2003, Mondy and Usseglio-Polatera 2013; see also the review by Menezes et al 2010). In a recent comparative study, Marzin et al (2012) suggested that functional trait-based metrics might discriminate anthropogenic disturbances better than taxonomy-based metrics, but very few investigators have used a functional trait-based approach to examine invertebrate community recovery after disturbance cessation (Rabeni et al 1985, MacLeod et al 2008.…”
mentioning
confidence: 99%